NEUROPROTECTIVE EFFECT CORILAGIN IN SPINAL CORD INJURY RAT MODEL BY INHIBITING NUCLEAR FACTOR-KB, INFLAMMATION AND APOPTOSIS - Zhang, Hong-xing; Liu, Feng-wei; Ren, Fei; Zhang, Yan-li; Nie, Zhong (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Neurological functions get altered in a patient suffering from spinal cord injury (SCI). Present studyevaluates the neuroprotective effect of corilagin in spinal cord injury rats by inhibiting nuclear factor-kappa B (NF-κB),inflammatory mediators and apoptosis.Materials and method: Spinal cord injury was produced by mechanical injury to spinal cord. All the rats were treated withcorilagin (10 & 15 mg/kg, ip) for the duration of 4 week. Neurological functions were evaluated in all the rats byBasso,Beattie and Brenahan scale (BBB scale). Moreover, at the end of treatment rats were sacrificed and expression ofNF-κB, concentration of cytokines like Tumor necrosis factor α (TNFα) & interlukin-6 (IL6) and oxidative stressparameters like Malondialdehyde (MDA) and toal antioxidant capacity (TAC) in spinal tissue of spinal cord injured rats.Immunohistological study was also performed to assess the apoptosis of neuronal cell.Result: There were significant (p<0.01) increase in BBB score and decrease in delayed response to pain in corilagin treatedgroup compared to SCI group. It was also observed that treatment with corilagin significantly (p<0.01) decreases theconcentration of TNF α, IL 6 & MDA in spinal tissues than SCI group. Moreover, it also decreases the TAC in spinaltissues compared to spinal cord injured rats and also ameliorates the altered expressions of NF-κB. Immunohistochemicalresult suggested that treatment with corilagin decreases the number of caspase-3 & Bax positive stain cell and increase inBcl-2 positive stained cell than spinal cord injured rats. Thus, corilagin decreases the apoptosis of neuronal cell in spinalcord injured rats.Conclusion: This study concludes the neuroprotective effect of corilagin in spinal cord injured rats by decreasingcytokines, oxidative stress & expression of NF-κB in spinal tissues and thereby decreases the apoptosis of neuronal cells.